Analisis Perbandingan Kinerja Keuangan Bank Konvensional dan Bank Syariah - Norfa A. Yusuf; Prof. Dr. Rusman Soleman; Dwi Yana Amalia Sari Fala (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
The objectives of this study are: To analyze the comparison of the financial performance of conventional banks and Islamic banks. The population used in this study were 10 conventional banks and Islamic banks registered with the Financial Services Authority (OJK). The type of data used in this study is quantitative data and data analysis using the SPSS 25 application. The methods used are descriptive statistical analysis, independent sample t-test and mann whitney test. The results of this study indicate that there are significant differences that can be identified between the financial performance of conventional banks and Islamic banks in the CAR, and NPL variables, while in the ROA, and LDR variables there is no difference.